Long-Term Hypercaloric Diet Consumption Exacerbates Age-Induced Dysmetabolism and Carotid Body Dysfunction: Beneficial Effects of CSN Denervation - Melo, Bernardete F.; Sacramento, Joana F.; Capucho, Adriana M.; Sampaio-Pires, Dinis; Prego, Cláudia S.; Conde, Silvia V. (Frontiers in Physiology, 2022)
The carotid bodies (CBs) are metabolic sensors whose dysfunction is involved in the genesis of dysmetabolic states. Ageing induces significant alterations in CB function prompting also to metabolic deregulation. On the other hand, metabolic disease can accelerate ageing processes. Taking these into account, we evaluate the effect of long-term hypercaloric diet intake and CSN resection on aged induced-dysmetabolism and CB function. Experiments were performed in male Wistar rats submitted to 14 or 44 weeks of high-fat-high-sucrose (HFHSu) or normal chow (NC) diet and submitted to either carotid sinus nerve (CSN) resection or sham procedure. After surgeries, animals were kept on diet for more 9 weeks. Metabolic parameters, basal ventilation and hypoxic and hypercapnic ventilatory responses were evaluated. CB type I and type II cells, HIF-1α and insulin receptor (IR) and GLP-1 receptor (GLP1-R) positive staining were analyzed by immunofluorescence. Ageing decreased by 61% insulin sensitivity in NC animals, without altering glucose tolerance. Short-term and long-term HFHSu intake decreased insulin sensitivity by 55% and 62% and glucose tolerance by 8% and 29%, respectively. CSN resection restored insulin sensitivity and glucose tolerance. Ageing decreased spontaneous ventilation, but short-term or long-term intake of HFHSu diet and CSN resection did not modify basal ventilatory parameters. HFHSu diet increased hypoxic ventilatory responses in young and adult animals, effects attenuated by CSN resection. Ageing, hypercaloric diet and CSN resection did not change hypercapnic ventilatory responses. Adult animals showed decreased type I cells and IR and GLP-1R staining without altering the number of type II cells and HIF-1α. HFHSu diet increased the number of type I and II cells and IR in young animals without significantly changing these values in adult animals. CSN resection restored the number of type I cells in HFHSu animals and decreased IR positive staining in all the groups of animals, without altering type II cells, HIF1α or GLP-1R staining. In conclusion, long-term hypercaloric diet consumption exacerbates age-induced dysmetabolism and both short and long-term hypercaloric diet intake promotes significant alterations in CB function. CSN resection ameliorates these effects. We suggest that modulation of CB activity is beneficial in exacerbated stages of dysmetabolism.